Antifungal Activity of Faloak (Sterculia comosa Wallich) Extractives - Fabianus Ranta; Deded S Nawawi; Eko S Pribadi; Wasrin Syafii (Masyarakat Peneliti Kayu Indonesia, 2012)
Faloak (Sterculia comosa Wallich) is a specific species of dry land that has potential antifungal. This study aims to determine the toxicity of barks, leaves, and seeds extracts as an antifungal, and to identify its bioactive compound. The extracts were prepared by multi stage maceration method. Antifungal activity was tested by agar well diffusion method, and minimum inhibition concentration (MIC) and minimum fungicide concentration (MFC) by two-fold serial dilution method were measured. Bioactive compound of active fraction were identified by Liquid Chromatography Mass Spectroscopy (LCMS), Fourier Transform Infrared (FTIR), and Nuclear Magnetic Resonance (NMR). Results showed that the diethyl ether (DE) fraction of seeds is more effective in inhibiting of Candida albicans growth, than the other fractions. Subfraction of DE7 has a higher potency in inhibiting the growth of of Candida albicans. Based on the analysis by LCMS, FTIR and proton NMR, the DE7 sub fractions contain 3-hydroxyoctadecanoic acid (C18H36O3), which is suggested as a mainly compound responsible for antifungal activity.Key words: antifungal, Candida albicans, extractive, Sterculia comosa